Strategi Pemasaran Kue Rumahan Di Timur Indah 5 Kota Bengkulu - Ramdhani, Heru (Jurnal Kewirausahaan dan Bisnis, 2024)
A home-based business is any type of business that can be run at home. Business operations are carried out at home, such as marketing products, buying and selling transactions, storing inventory, and others. Therefore, a community service program with the title "Marketing Strategy for "Home-Baked Cakes in Timur Indah 5 Bengkulu City" was carried out to assist business managers in designing marketing strategies that are in accordance with the characteristics of their business. This program aims to increase product sales and introduce bricks to the community. The implementation of marketing strategies is carried out with several steps, such as creating a brand identity for the Kue Rumahan business, using social media as a means of promotion, and developing a distribution network. Brand identity was created to introduce Kue Rumahan more clearly and contemporary among the public, while the use of social media was carried out so that consumers can easily recognize and remember the good use of Kue Rumahan ingredients. The development of a distribution network was carried out to expand the market share and expand the product's reach to consumers. From the evaluation results, the community service program with the title "Marketing Strategy for Home-Baked Cakes in Timur Indah 5 Bengkulu City" succeeded in having a positive impact on the continuity of the MSME business. The implementation of the right marketing strategy has succeeded in increasing the number of product sales and increasing awareness of home-made cakes in the community. In addition, this program also helps MSMEs to expand distribution networks and optimize the use of social media as a means of promotion. Thus, the implementation of effective marketing strategies can be a solution for MSMEs in facing increasingly competitive market competition.